QUALITY IMPROVEMENT AT PACKAGING STATION IN PT PETROSIDA GRESIK WITH SIX SIGMA METHOD - Gama Kiswara, Afrizal
PT Petrosida Gresik is an agribusiness company that produces various types of pesticides. At present, the SIDAFOS 480SL 1 L product which is the company's flagship product has a defect rate of 0.5% exceeding the company's target of 0.1%. The company wants to reduce the number of defects in the product. This study aims to provide quality improvement proposals at the SIDAFOS 480SL packaging station at PT Petrosida Gresik. The proposed quality improvement is intended to reduce the defective product SIDAFOS 480SL 1 L. To make improvements used the six sigma methodology with the DMAIC cycle approach, namely define, measure, analyze, improve and control. At the define stage the research object is determined, namely the SIDAFOS 480SL packaging station and the SIDAFOS 480SL 1 L. product packaging. At this stage, the defect factors are determined using the Delphi method and the critical factors are determined. In the measure phase, the stability and capability of the packaging process are measured with a sigma value of 3.03. During the analyze phase, the root cause analysis is carried out, and the critical root problems are found: (a) there is no induction time duration, (b) the engine indicator is not clearly visible, and (c) there are no seal stick removal instructions. During the improve phase, several proposed improvements are made: (a) determining the duration of the standard induction of the bottle sealer machine, (b) adding a sound mechanism to the bottle sealer machine, and (c) improving the working instructions of the bottle sealer machine. To guarantee implementation, a timeline and SOP for bottle sealer machines were made at the control stage.